Preliminary study for the prevalence and causes of anemia in pregnant women attending an Antenatal Care Unit in different periods of gestation - Thongperm, Wararat; Chaisen, Mantana; Chunchom, Yuttana; Aueduldecha, Supakit; Sarakul, Orawan (Journal of Associated Medical Sciences, 2018)
Background: One of common complications of pregnancy is an anemia which is effected by various causes. Anemia can develop throughout the pregnancy period and increase in severity upon the gestation times. WHO recommends all pregnant women should attend an antenatal care (ANC) unit in the first trimester of gestation for healthy promotion and complication prevention during pregnancy and after birth. Objectives: The aim of this preliminary study is to find out the prevalence and causes of anemia in pregnant women who start attending an ANC program at different time points of gestation. Materials and methods: Cross-sectional study was performed during May 2015 -February 2016. Hematological parameters were examined in all 190 pregnant women attended the ANC unit at Nayong Hospital. Participants were divided into three groups according to period of gestation at the first time of ANC admission. Serum ferritin, thalassemia screening, and hemoglobin typing were determined in anemia cases to analyze causes of anemia. Prevalence of anemia at each time point ANC attended groups were calculated. Mann-Whitney U test was used to compare the different of parameters between the groups. Results: Prevalence of anemia in all attended pregnant women was 22.1%. According to the period of gestation at the first time of ANC admission, the prevalence of anemia was 17.2% (15 of 87) at the first trimester group, 22.5% (20 of 89) at the second trimester, and 50.0% (7 of 14) at the third trimester group. Levels of hemoglobin and hematocrit of the second and the third groups were significantly different from the first trimester group with p<0.05. MCHC of the third trimester group showed significantly different from both the first and second trimester groups, p<0.05. Causes of anemia were thalassemia/abnormal hemoglobin carriers in 11 cases (5.8%), Iron deficiency anemia (IDA) in 10 cases (5.3%), IDA with thalassemia/abnormal hemoglobin carriers in 6 cases (3.2%), and anemia with other causes in 15 cases (7.9%). For thalassemia cases, HbE trait without α-thalassemia had the highest prevalence (44.4%). There were two cases of severe anemia, which were Hb H-CS disease and IDA. Conclusion: Prevalence of anemia in pregnant women in this presentation was still high and increased throughout the period of gestation. Causes of anemia, such as IDA, can be prevented by early attention to an ANC unit. The promotion of an ANC program for married couples and adolescent women should be considered to improve maternal and fetal health quality during pregnancy and after-birth.